2014
DOI: 10.1038/ncomms4377
|View full text |Cite
|
Sign up to set email alerts
|

Carrier localization and electronic phase separation in a doped spin-orbit-driven Mott phase in Sr3(Ir1–xRux)2O7

Abstract: Interest in many strongly spin-orbit-coupled 5d-transition metal oxide insulators stems from mapping their electronic structures to a J eff ¼ 1/2 Mott phase. One of the hopes is to establish their Mott parent states and explore these systems' potential of realizing novel electronic states upon carrier doping. However, once doped, little is understood regarding the role of their reduced Coulomb interaction U relative to their strongly correlated 3d-electron cousins. Here we show that, upon hole-doping a candida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 32 publications
11
81
0
Order By: Relevance
“…Given the apparent occurrence of these two competing magnetic structures and no evidence for structural phase separation we assign the behavior as being due to electronic phase separation. This conclusion is in line with that arrived at from the Raman investigation of Sr 2 Ir 1−x Ru x O 4 16 and also the Ru doping behavior in the related iridate Sr 3 Ir 2 O 7 25 . We note, however, the intriguing similarity of the magnetic structure to the ortho-G-AF phase presented in Ref.…”
Section: Experimental Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Given the apparent occurrence of these two competing magnetic structures and no evidence for structural phase separation we assign the behavior as being due to electronic phase separation. This conclusion is in line with that arrived at from the Raman investigation of Sr 2 Ir 1−x Ru x O 4 16 and also the Ru doping behavior in the related iridate Sr 3 Ir 2 O 7 25 . We note, however, the intriguing similarity of the magnetic structure to the ortho-G-AF phase presented in Ref.…”
Section: Experimental Methodssupporting
confidence: 80%
“…The evolution and coexistence of long ranged magnetically ordered structures in the series Instead we find electronic phase separation to be the most consistent scenario for the coexistence of M1 and M2 based on our results and in analogy to separate investigations 16,17,25 . One potential cause of this phase separation, that manifests in coexisting magnetic structures, is a competing and delicate balance of magnetic interactions in the Sr 2 Ir 1−x Ru x O 4 system due to altered exchange pathways.…”
Section: Discussionmentioning
confidence: 62%
“…These weak violations were later confirmed to be of structural origin via a polarized neutron scattering study 19 and are reminiscent of those observed within the n = 1 system Sr 2 IrO 4 (also via neutron diffraction). In this paper, we utilize single crystal neutron scattering and rotational anisotropy second harmonic generation (RA-SHG) measurements to resolve the structure of Sr 3 Ir 2 O 7 .…”
mentioning
confidence: 77%
“…3 shows RA-SHG patterns from ). 19 For the non-centrosymmetric 2mm point group, we assume the dominant contribution to SHG to be of bulk electricdipole origin. For the centrosymmetric 4/mmm and mmm point groups on the other hand, bulk electricdipole SHG is forbidden, and we instead assume the dominant contribution to be of bulk electric-quadrupole origin, consistent with the case for Sr 2 IrO 4 .…”
mentioning
confidence: 99%
“…In metallic spin glass systems, the interplay between weak ferromagnetism and spin glass order is known to yield a similar response 36 , which when combined with the ZFC cusp observed at T F supports the notion of a spin glass state at low temperature in doped samples. Meanwhile, the rapid suppression of the high field M (H) with La-substitution reflects the doping-driven suppression of the parent AF magnetic state via a diminishing ordered moment or a rapidly reduced ordered volume fraction within a phase separated ground state 37 . Curie-Weiss fits of the form χ(T ) = C T −Θ + χ 0 plotted in Fig.…”
Section: Magnetization Measurementsmentioning
confidence: 99%